Dynamic and flow instability analysis during runaway process for a pump turbine - Yanyan Li; Longgang Sun; Pengcheng Guo; Zhuofei Xu (Engineering Applications of Computational Fluid Mechanics, 2024)
A power failure in the pump condition combined with the rejection of the guide vanes can cause the unit to runaway, which represents a dangerous transitional process for pumped storage power stations. This process is accompanied by intense oscillations in internal flow, pressure fluctuations, and changes runner forces. This study aims to clarify the unstable flow characteristics during the runaway process by focusing on the transient behaviour from the pump condition to the runaway condition in a high-head model pump turbine. The numerical calculation of the runaway speed and discharge are consistent with experimental test results. The results indicate that the dynamic curve is not continuously stable during the process but exhibits dynamic oscillations before reaching a relatively stable condition. Significant pressure fluctuations with high amplitudes are observed in the pump braking zone and close the runaway condition. Further analysis reveals low frequency, high amplitude pressure fluctuations within various flow components at frequencies smaller than the runner rotational frequency (fn). Axial forces demonstrate a linear correlation with the change rate of discharge. The dynamic evolution of the backflow vortex at the runner inlet is the main cause of significant fluctuations in the axial forces of the runner. The scale of the backflow vortex gradually increases as the discharge decreases, peaking in the pump braking zone. Entering the turbine operating condition, its intensity decreases to some extent but with a significantly expanded range. Near the optimal operating condition, the internal flow around the runner becomes smooth. As the discharge further decreases, the backflow vortex scale gradually increases, eventually forming a ring structure at the runner inlet. Further analysis indicates that the dynamic evolution of the backflow vortex at the runner inlet inevitably disrupts the flow, leading to a significant increase in pressure fluctuation amplitudes and more pronounced oscillations in axial forces.